Identifikasi Keanekaragaman Makroalga Yang Tersebar di Perairan Pulau Jawa - Alfamela Putri; Siti Qadarsih Melandari; Ovi Mariska; Melly Putri Gustiarni; Tri Widya Edelwis (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2023)
Algae, also known as Sea weeds, has the scientific name algae or grass. Seaweed is a type of algae that contains chlorophyll. To date, there are about 9,600 species of macroalgae recorded worldwide. Regarding the purpose of recording this article is to identify the diversity of macroalgae spread in the waters of Java Island. The research used the literature review method by analyzing several macroalgae articles located on the island of Java with a span of 2018 to 2023. Steps in identifying 20 articles: 1) conduct a literature search for articles and journals on macroalgae diversity in the waters of Java island, 2) identify macroalgae diversity contained in the results of 20 literature articles. Based on the results of the review that has been carried out, it can be summarized that are very many species of macroalgae, especially algae or seaweed spread on the island of Java. There are several algae that are used as medicinal ingredients and functional foods.